Análise das oportunidades de aprendizagem em aulas expositivo-participativas: estudo de caso de um professor de Biologia - Camargo, Cristiane Cordeiro de (2005)
This work is inserted in an investigative line, guided by a cognitive learning framework, seeking to understand how speech, in the teaching environment, has impact upon the learning process of students. Using as outline suggested questions from the teacher in participative lectures and the reactions to the students responses, this investigation aimed to answer two questions: a) How does the analysis of the interaction teacher-student in participative lectures enable the identification of possible learning opportunities? b) Which are the variables involved in the process that go from the intentions in teaching practice, to the opportunities of learning offered? To proceed in this analysis, we have sought reference in social-historical psychology authors regarding the caracterization of the thought process and the structure of scientific knowledge ( Petrovsky, 1980; Vygostky, 1993 ); authors who, using as a starting point social-historical psychology, have developed concepts and interpretations on the functions of speech in learning activities ( Scott, 1998; Mercer, 1996; Wegerif et al, 1999 ); authors who deal with forms of relationship in regard to knowledge, as they materialize in the teaching environment ( Edwards, 1997 ). This work is characterized as a descriptive-analytic study of a biology teacher; of qualitative nature, presented in case study format. The data was collected thru means of observation and registry of given lectures as well as an interview with the teacher. Results indicate that the identification of learning opportunities offered by the teacher, by means of interventions, can only be comprehended if articulated to the logics of context ( structure of scientific concepts ) and interaction ( structure of participation, that is, the implied rules that guide the students and teacher s participation in their speech during class). These opportunities sometimes don t correspond to the ones idealized /verbalized by the teacher, as they suffer influence of many variables in the process of materialization in class. Among these are the ones related to the basis of knowledge of the teacher in teaching skills, in terms of knowledge of a specific area as well as in the pedagogic area. A correct articulation between the two types of knowledge can enable a more adequate one between the teacher s interventions and the mental processes necessary to the elaboration of certain scientific knowledge by the students. Beyond that, results also show the utility of theoretical structures, deriving from concepts such as scafolding ( Bruner et al, 1976, apud Scott, 1998 ) for the analysis of concrete situations in teacher-student interaction during participative lectures.